Colonic catabolism of dietary phenolic and polyphenolic compounds from Concord grape juice - Stalmach, A.; Edwards, Christine; Wightman, J.; Crozier, A. (2013)
After acute ingestion of 350 ml of Concord grape juice, containing 528 µmol of (poly)phenolic compounds, by healthy volunteers, a wide array of phase I and II metabolites were detected in the circulation and excreted in urine. Ingestion of the juice by ileostomists resulted in 40% of compounds being recovered intact in ileal effluent. The current study investigated the fate of these undigested (poly)phenolic compounds on reaching the colon. This was achieved through incubation of the juice using an in vitro model of colonic fermentation and through quantification of catabolites produced after colonic degradation and their subsequent absorption prior to urinary excretion by healthy subjects and ileostomy volunteers. A total of 16 aromatic and phenolic compounds derived from colonic metabolism of Concord grape juice (poly)phenolic compounds were identified by GC-MS in the faecal incubation samples. Thirteen urinary phenolic acids and aromatic compounds were excreted in significantly increased amounts after intake of the juice by healthy volunteers, whereas only two of these compounds were excreted in elevated amounts by ileostomists. The production of phenolic acids and aromatic compounds by colonic catabolism contributed to the bioavailability of Concord grape (poly)phenolic compounds to a much greater extent than phase I and II metabolites originating from absorption in the upper gastrointestinal tract. Catabolic pathways are proposed, highlighting the impact of colonic microbiota and subsequent phase II metabolism prior to excretion of phenolic compounds derived from (poly)phenolic compounds in Concord grape juice, which pass from the small to the large intestine.